Menyingkap Trauma Pelecehan Seksual terhadap Laki-laki pada Film Dear David - Damayanti, Elsa; Sevilla, Vinta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
As a mass media outlet, films are entertaining and provide information for the public. This research examines the film Dear David, which was shown on a digital platform and directed by Lucky Kuswandi and intended to convey a message about men being victims of sexual harassment. This research aims to determine the representation of sexual harassment towards men conveyed in a film. This research uses Roland Barthes' semiotic theory to analyze the representation of sexual harassment against men in the film Dear David. Seven scenes were found that depicted the reality of sexual harassment experienced by the character and ended up causing trauma. The results of this research are the issue of sexual harassment by men where there is a stigma of toxic masculinity, which emphasizes that men are strong and should not appear weak so that patriarchal culture means that victims are often ignored and do not receive attention.